Cluster Analysis of Himachal Tomato - Sharan, Girija; Madhavan, T; Rawale, Kishor (Journal of Agricultural Engineering, 2002)
A crate of Himachal tomato was obtained from Azad Mandi, Delhi. It contained 252 fruits. Each fruit was weighed and its axial dimension measured. Data of all 252 fruits was then subjected to cluster analysis, using weight and axial dimension separately as basis. The tool of Cluster Analysis enables us to divide the sample in groups that are relatively homogeneous in size on the basis of weight or axial dimensions, whichever is desired. Analysis also yields mass proportion of tomato contained in each group as also the number. The utility of cluster analysis lies in the fact that it can indicate how many homogenous groups can be made of a lot of ungraded produce in advance and what will be the physical characteristics of produce in each group. This will be useful to those designing size graders for tomato, other fruits and vegetables..